Resistance to insecticides and effect of synergists on permethrin toxicity in Pediculus capitis (anoplura: Pediculidae) from Buenos Aires - Picollo, Maria Ines (2000)
Permethrin-resistant colonies of Pediculus capitis (De Geer) from Buenos Aires were used to establish a resistance profile and to examine resistance mechanisms. All permethrin-resistant head lice (resistance ratio from 52.8 to >88.7) were also resistant to d-phenothrin (resistance ratio from 40.86 to >48.39) and deltamethrin (resistance ratio from 16.24 to 38.06). No cross-resistance to carbaryl was found in any of the pyrethroid-resistant P. capitis tested. Otherwise, all resistant colonies showed low to high levels of resistance to β-cypermethrin. This pyrethroid had never been applied as a pediculicide in Argentina; however, the high level of resistance found in these permethrin-resistant colonies (resistance ratio from 9.74 to 50.97) demonstrated that pyrethroid cross-resistance occurred to this novel insecticide. Treatment with piperonyl butoxide (PBO) or triphenylphosphate (TPP) significantly decreased the toxicity of permethrin in the four colonies tested. The esterase inhibitor TPP produced lower enhancement of toxicity than the multifunction oxidase inhibitor PBO in the colonies having the highest resistance levels. Results presented here concerning the cross-resistance profile and synergism by enzyme inhibitors in permethrin-resistant head lice demonstrated that enhanced metabolism was involved in the pyrethroid resistance. However, the substantial degree of resistance that remained after synergism suggested the presence of another resistance mechanism. Cross-resistance to pyrethroid and susceptibility to the carbamate carbaryl suggested a common action mechanism.